PENGARUH PENERAPAN SISTEM PENGENDALIAN INTERN PEMERINTAH, SISTEM AKUNTANSI KEUANGAN DAERAH, PEMANFAATAN TEKNOLOGI INFORMASI, DAN KOMPETENSI APARATUR TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Kasus Pada Dinas Kesehatan Kabupaten Karo) - Purnama Sari Br Sinulingga; Arthur Simanjuntak; Mitha Christina Ginting (JURNAL MANAJEMEN, 2022)
This study aims to examine the effect of applying the government's internal control system, regional financial accounting system, utilization of information technology, and apparatus competence simultaneously on the quality of local government financial reports at the Karo District Health Office. In this research method, the type of research used is causal associative research with a quantitative approach. The population in this study were all employees at the Karo District Health Office whose sampling technique used the saturated sampling technique. The data analysis method used is multiple linear regression with the help of SPSS 25. The analysis process carried out is data quality test, classical assumption test, and hypothesis testing. Based on the results of the study, it was found that the implementation of the government's internal control system had a significant positive effect on the quality of local government financial reports at the Karo District Health Office, the regional financial accounting system had a significant positive effect on the quality of local government financial reports at the Karo District Health Office. The use of information technology has a significant positive effect on the quality of local government financial reports at the Karo District Health Office. Apparatus competence has a positive and insignificant effect or in other words does not significantly affect on the quality of local government financial reports at the Karo District Health Office.